Multilocus Sequence-Typing of Anthrax Microbe Strains Isolated in Russia and Neighboring Countries - Yu. O. Goncharova; I. V. Bakhteeva; R. I. Mironova; A. G. Bogun; K. V. Khlopova; V. S. Timofeev (Проблемы особо опасных инфекций, 2021)
Objective – genotyping by multilocus sequence-typing (MLST) and phylogenetic analysis of 40 Bacillus anthracis strains isolated in Russia and neighboring countries.Materials and methods. In this study, the sequences of seven housekeeping genes of B. anthracis strains were assembled based on the data of a whole genome new generation sequencing, after which the identified mutations and their coordinates were described. The obtained sequences were used for genotyping of the investigated sample using the MLST method. The results are compared with the data presented in PubMLST database. A phylogenetic analysis was performed for the in silico fused sequences of the seven loci of the identified sequence types. The MEGA 7.0 software package was used to build the dendrograms.Results and discussion. Two sequence types (ST) have been found in the examined sample: 35 strains belong to ST-1, and five strains that differed by one common mutation at the glpF locus – to ST-3 (according to PubMLST coding), which emphasizes the genetic separation of this group of strains. One strain has a unique mutation in the gmk gene located outside the region used for MLST.